2007
DOI: 10.1586/14760584.6.6.913
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant lentivector as a genetic immunization vehicle for antitumor immunity

Abstract: SummaryEncouraged by remarkable successes in preventing infectious diseases and by the well established potential of immune system for controlling tumor growth, active therapeutic immunization approaches hold great promise for treating malignant tumors. In recent years, engineered recombinant viral vectors have been carefully examined as genetic immunization vehicles and have been demonstrated to induce potent T cell mediated immune responses that can control tumor growth. Very recent efforts suggest that lent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 100 publications
0
22
0
Order By: Relevance
“…Lentivirus-based vectors have several properties that offer distinct advantages over current vectors used in clinical trials [99,100]. Lentivirus-based vectors are typically less immunogenic as most genes encoding viral proteins have been removed, thereby allowing for the repeated use of these vectors for immunization without inducing pre-existing immune responses against the vector.…”
Section: Bacterial and Viral Vectorsmentioning
confidence: 99%
“…Lentivirus-based vectors have several properties that offer distinct advantages over current vectors used in clinical trials [99,100]. Lentivirus-based vectors are typically less immunogenic as most genes encoding viral proteins have been removed, thereby allowing for the repeated use of these vectors for immunization without inducing pre-existing immune responses against the vector.…”
Section: Bacterial and Viral Vectorsmentioning
confidence: 99%
“…Therefore, lentivectors have thus been proposed to be an ideal vector tool for vaccine delivery. 20,[24][25][26][27][28][29][30][31][32][33] Based on the study of Sindbis virus, a member of the Alphavirus genus and the Togaviride family, we have reported a mutant Sindbis virus glycoprotein, (SVGmu) which can specifically bind to DC-specific intracellular adhesion molecule (ICAM) 3 grabbing non-integrin (DC-SIGN, CD209). 34 DC-SIGN is a C-type lectin-like receptor and is expressed on DCs and macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we and others have shown that recombinant lentivector effectively transduced dendritic cells (DCs) in vitro and in vivo and stimulated more potent and longer lasting Ag-specific CD8 T cell immune responses than other viral vectors, as well as other genetic immunization approaches such as naked plasmid DNA (12–17). The potency and durability of lentivector-induced immune responses may be related to the vector’s capacity to efficiently transduce nondividing skin DC subsets without compromising their Ag processing and presenting function in vivo (12, 18, 19).…”
mentioning
confidence: 99%